2013
DOI: 10.1111/bjh.12671
|View full text |Cite
|
Sign up to set email alerts
|

Community‐acquired infections associated with increased risk of lymphoplasmacytic lymphoma/Waldenström macroglobulinaemia

Abstract: Summary Emerging evidence supports the role of immune stimulation in the development of lymphoplasmacytic lymphoma/Waldenström Macroglobulinaemia (LPL/WM). Using the population-based Surveillance, Epidemiology End Results-Medicare database we investigated the exposure to 14 common community-acquired infections and subsequent risk of LPL/WM in 693 LPL/WM cases and 200 000 controls. Respiratory tract infections, bronchitis (odds ratio (OR) 1.56), pharyngitis (OR 1.43), pneumonia (OR 1.42) and sinusitis (OR 1.33)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…In another study based on German claims data, Kolditz et al [11] found that a malignant neoplasms were associated with a 32% increased risk of CAP. In three studies from the United States based on the population-based Surveillance, Epidemiology End Results (SEER)-Medicare database, an elevated risk of pneumonia (27 to 42%) was found for different types of hematological malignancies [1214].…”
Section: Discussionmentioning
confidence: 99%
“…In another study based on German claims data, Kolditz et al [11] found that a malignant neoplasms were associated with a 32% increased risk of CAP. In three studies from the United States based on the population-based Surveillance, Epidemiology End Results (SEER)-Medicare database, an elevated risk of pneumonia (27 to 42%) was found for different types of hematological malignancies [1214].…”
Section: Discussionmentioning
confidence: 99%
“…Large epidemiological studies have shown clear associations between infections and monoclonal B-cell lymphocytosis (MBL) and CLL, non-Hodgkin lymphoma (NHL), and MM. [53][54][55] More recently, the commensal bacterial flora of the gut (microbiota) has also been implicated in lymphomagenesis. 12 The expression of restricted immunoglobulin gene repertoires/B-cell receptors (BCR) in CLL and malignant lymphomas underscores a key role of an antigenic drive in the initiation and perpetuation of lymphoproliferation; mainly microbial antigens but also self-antigens released on cell apoptosis.…”
Section: Infection-induced Lymphoid Malignanciesmentioning
confidence: 99%
“…We observed increased mortality risks for certain infections (Clostridium difficile enterocolitis, mycoses/protozoal infections, viral hepatitis, HIV and respiratory tract infections) and specific digestive diseases (chronic liver diseases, gastrointestinal bleeding and vascular diseases of the intestine and colon). Previous studies have reported that viral hepatitis, HIV and respiratory tract infections are rare but important risk factors for LPL/WM, which could account for increased mortality due to these infections (Koshiol et al, 2008;Giordano et al, 2009;Kristinsson et al, 2010;Vajdic et al, 2014;Nipp et al, 2014;Gibson et al, 2014;McShane et al, 2014). Additional factors that may have contributed to increased risk of infection-related mortality include longterm disease and treatment-related immunosuppression (Hern andez-D ıaz & Garc ıa Rodr ıguez, 2001;Karlsson et al, 2011;Rao & Faso, 2012;Narum et al, 2014;Olszewski et al, 2017;Caplan et al, 2017), recurrent/increased antimicrobial and corticosteroid use and/or exposure to healthcare settings (particularly for Clostridium difficile enterocolitis and mycoses/protozoal infections) (Revolinski & Munoz-Price, 2018;Varughese et al, 2018), and chemotherapy use leading to hepatitis virus re-activation (Yeo et al, 2000; European Association for the Study of the Liver, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Cardiovascular, infectious and neurological conditions have been identified as the most common noncancer causes of death (Garc ıa-Sanz et al, 2001;Kastritis et al, 2015;Castillo et al, 2015b), but these risks have not been quantified compared to the general population, and information on more specific and other causes of death is sparse. Data are lacking on mortality patterns for LPL versus WM patients, which could differ due to the presence of IgM gammopathy, and for other factors associated with developing LPL/WM, such as hepatitis C virus (Giordano et al, 2009;Nipp et al, 2014), human immunodeficiency virus (HIV; Koshiol et al, 2008;Gibson et al, 2014) or respiratory tract infections (Kristinsson et al, 2010;McShane et al, 2014).…”
mentioning
confidence: 99%